2016
DOI: 10.1080/14740338.2017.1267725
|View full text |Cite
|
Sign up to set email alerts
|

The safety of nivolumab for the treatment of advanced non-small cell lung cancer

Abstract: Immune checkpoint blockaders (ICBs) act by unbalancing the immune system, thus favoring the development of an immune-mediated antitumor effect. ICBs targeting the programmed cell death receptor-1 (PD-1) have recently been investigated in a number of advanced tumors, including non-small cell lung cancer (NSCLC). Nivolumab, a fully human IgG4 kappa directed against PD-1, has been the first ICB to be approved for second-line treatment of advanced NSCLC. Areas covered: In this review we focus on the clinical devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The PD-L1 inhibitor durvalumab has been reported to be effective against stage III NSCLC when used after chemoradiotherapy (6). As these drugs are associated with serious and potentially fatal immune-related adverse events (irAE) (7)(8)(9), patients treated with immune checkpoint inhibitors must be monitored carefully. The recent development of checkpoint inhibitors has increased the number of treatment options for various types of cancer, and clinicians can have difficulty choosing the optimal agent.…”
mentioning
confidence: 99%
“…The PD-L1 inhibitor durvalumab has been reported to be effective against stage III NSCLC when used after chemoradiotherapy (6). As these drugs are associated with serious and potentially fatal immune-related adverse events (irAE) (7)(8)(9), patients treated with immune checkpoint inhibitors must be monitored carefully. The recent development of checkpoint inhibitors has increased the number of treatment options for various types of cancer, and clinicians can have difficulty choosing the optimal agent.…”
mentioning
confidence: 99%
“…Although ICIs, including antibodies against PD-1/PD-L and CTLA-4, have yielded satisfying outcomes in terms of patient survival, they can also disrupt self-tolerance and lead to unique irAEs [ 43 , 44 ]. With the widespread application of ICIs in patients with advanced malignant tumors, irAEs caused by ICIs have been adequately discussed in a series of clinical trials [ 45 , 46 ]. Translational studies have shown that multiple pathways, such as cytokine, autoreactive T-cell and autoantibody pathways, may affect the development of irAEs [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) might have modified the immune response associated with the paraneoplastic syndromes. Recently, ICIs have been widely used in cancer therapy, including lung cancer (16-18). However, ICIs are known to exacerbate preexisting autoimmune disease (19, 20).…”
Section: Discussionmentioning
confidence: 99%